2005
DOI: 10.4319/lo.2005.50.3.0978
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between species richness and taxonomic distinctness in freshwater organisms

Abstract: Taxonomic distinctness is a newer biodiversity measure that emphasizes the average taxonomic relatedness between species in a community. We examined whether species richness (SR) and taxonomic distinctness (TD) were significantly related and whether they showed similar environmental relationships in regional data sets for various groups of freshwater organisms, ranging from lake mollusks and fishes to stream diatoms and invertebrates. We found that the relationship between SR and TD varied widely, ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
74
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 51 publications
12
74
2
6
Order By: Relevance
“…This accords with recent observations obtained mainly from aquatic fauna datasets (e.g. Ellingsen et al 2005, Heino et al 2005. In particular, one taxonomic category may not be a reliable surrogate for biodiversity in another, nor the group as a whole.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This accords with recent observations obtained mainly from aquatic fauna datasets (e.g. Ellingsen et al 2005, Heino et al 2005. In particular, one taxonomic category may not be a reliable surrogate for biodiversity in another, nor the group as a whole.…”
Section: Discussionsupporting
confidence: 79%
“…Hence, one phylum is not necessarily a reliable surrogate for another or for overall biodiversity, nor are patterns necessarily the same for different metrics. Similar findings emerged from a recent study of freshwater invertebrates, microflora (diatoms), bryophytes and fish (Heino et al 2005). Apart from this and an earlier study of diatoms (Izsak et al 2002), we are unaware of studies that have comprehensively examined relationships between S and Δ + in aquatic flora.…”
Section: Introductionsupporting
confidence: 54%
“…Heino et al, 2007;Milošević et al, 2012). In addition, Heino et al (2005) showed that number of species was variably related to + in Finland for a number of stream and lake organisms, with correlations ranging from significantly negative through nonsignificant to significantly positive. These results indicated TD indices could provide complementary information about the variability of biodiversity in addition to traditional diversity indices.…”
Section: Discussionmentioning
confidence: 99%
“…Studies like Heino et al (2005) showed that Taxonomic Distinctness also varies along natural gradients and it is unlikely that a site can be determined to be degraded or not degraded based only on the measure of Taxonomic Distinctness. On the other hand, although Average Taxonomic Distinctness has the ability to discriminate properly between polluted and non-polluted areas in those of low number of species (as it is the case of the subtidal communities in Mondego), the results of this study demonstrated that its power of discrimination decreases when the number or species increases (see confidence limits in the funnel graphic representation, Fig.…”
Section: Discussionmentioning
confidence: 99%